(untitled) (Journal of Dhaka National Medical College & Hospital, 2016)
Introduction: Mobile phone is the most common information access device which is one of the important wonders of modern science. The aim of this study was to find out the pattern of mobile phone usage and its health impact among the university students as young people are more likely than any other demographic group to use mobile phones and adopting mobile phones as an integral part of their daily lives. Method and materials: This cross sectional study was conducted from July 2014 to June 2015 on 440 students of Bangladesh University of Engineering and Technology (BUET), Dhaka University, BRAC University and Jagannath University. Data were collected by face to face interview and recorded in pretested written self-administered questionnaires. Results: The mean age of 440 respondents was about 22 ± 2.3 years. More than two-third (71%) of the respondents were male. Most of the respondents (63.4%) were under graduate, more than three-fourth (88%) of the respondents was unmarried. Two-third of the respondents (66%) used one mobile handset, more than half (55%) use smart phone. More than one-third (42%) of the respondents spend 0-3 hours over phone daily, More than one-third (38.6 %) using mobile phone for 3-5 years, more than half (54.3%) of the respondents spent 500 taka per month for maintaining mobile phone. All of the respondents (100%) used mobile phone for communication purpose, more than three-quarter (79.1%) of them used mobile phone also for net browsing, more than half used for playing games (55.9%) and for taking pictures (59.3%). More than one-third (39.32%) of the respondents faced different health problems such as inattentiveness (46.62%), headache (42.69%), insomnia (34.26%) and eye problems (24.71%). Conclusion: The main reason for using a mobile phone was for socializing, as well as for personal affair, safety and privacy purposes. There were some health impacts documented in this study. There should be more research in this topic as this study was done on a limited number of subjects J. Dhaka National Med. Coll. Hos. 2016; 22 (02): 31-35